STUDI PERKEMBANGAN PROPERTI PERUMAHAN GRAHA RAYA BINTARO TANGERANG SELATAN - Yudi, Christopher Hans Putraning; Bella, Priyendiswara Agustina; Tjung, Liong Ju (Jurusan Arsitektur dan Perencanaan, 2024)
Graha Raya Bintaro, established in 1997 with a land area of 350 hectares and having developed 2/3 of the total land, is the primary focus of this study titled